Monitoring of quality of professional and pedagogical activity and determination of criteria for its implementation - Bakatanova , V. (Problems of Engineer-Pedagogical Education, 2023)
In article relevant theoretical aspects and features of monitoring of quality of education and quality of professional activity of teachers of vocational school are revealed. The carried-out analysis of scientific sources allowed to reveal certain problems of implementation of monitoring of quality of activity of professional and pedagogical workers in institutions of professional education. In particular it is a problem of determination of criteria of quality for estimation of activity of teachers and training officers professional institutions of education. For the purpose of determination of such criteria expert assessment of factors which influence quality of professional and pedagogical activity for the sake of establishment of specific weight of each factor of influence and their further ranging was carried out. Expert assessment was carried out on the basis of technical training college No. 50 Karlivka of Poltava region, teachers and training officers to which acted as experts. The analysis of the data obtained from experts demonstrates that the theoretical model of factors of influence on quality of professional activity of teachers of professional school is constructed in general truly and the values of influence of each factor put in it have no essential differences from data of expert estimation. On the basis of processing of the obtained data criteria for carrying out monitoring of quality of professional and pedagogical activity of teachers of vocational school were defined. Such criteria can be considered: 1) implementation of continuous education of teachers; 2) ability and efficiency of implementation of theoretical and inservice training; 3) ability to keep the educational planning documentation; 4) support of corporate culture of educational institution (first of all - unity of pedagogical requirements); 5) social activity of teachers (participation in after-hour actions in educational institutions and beyond its limits). Prospects of further researches of this perspective consist in: implementation of monitoring of quality of professional and pedagogical activity of teachers of vocational school according to the revealed criteria; carrying out psychology and pedagogical researches of quality of vocational education in professional institutions of education and ways of implementation of its monitoring; in a research of quality of professional pedagogical education at its different stages.